Parental Social Bonds and Adolescents' Convictions. Issue 1 (2nd January 2019) - Nielsen, Alva Albæk
ABSTRACT: Social control theory suggests that adolescents are more likely to deviate when their parental bonds are weak or broken. However, are strong bonds to unconventional parents also a protective factor, or do they increase the risk of delinquency? There is almost no empirical evidence on this puzzle. Combining Danish survey and register data ( N  = 2, 677), this study uses fixed effects linear regressions and finds that parental convictions do not moderate the effect of strong parental social bonds. Rather, the main result shows that indirect supervision (mother knowing the adolescent's friends) reduces the risk of child conviction, irrespective of maternal conviction.